Communist takeover and occupation of Estonia. Special report no 3 of the Select Committee on communist aggression. House of Representatives 83rd congress, 2nd session. [... . Chairman: Charles J. Kersten] (United States Government Pr. Office, 1954)
Bibl. Committee print.